2022
DOI: 10.1186/s12951-022-01307-x
|View full text |Cite
|
Sign up to set email alerts
|

A roadmap to pulmonary delivery strategies for the treatment of infectious lung diseases

Abstract: Pulmonary drug delivery is a highly attractive topic for the treatment of infectious lung diseases. Drug delivery via the pulmonary route offers unique advantages of no first-pass effect and high bioavailability, which provides an important means to deliver therapeutics directly to lung lesions. Starting from the structural characteristics of the lungs and the biological barriers for achieving efficient delivery, we aim to review literatures in the past decade regarding the pulmonary delivery strategies used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 185 publications
0
23
0
1
Order By: Relevance
“…Direct exposure of LPS to the lungs not only triggers pulmonary inflammation but also promotes oxidative stress significantly. [ 21 ] Thus, the LPS‐induced ALI model was also selected, which is considered to be the inflammatory disease with high expression of iNOS/ROS. [ 6b,22 ] As shown in Figure S31, Supporting Information, the quantitative detection results of iNOS and ROS content showed that, the content of iNOS in the injured lungs of ALI mice was 25.8 × 10 −6 m , and there was almost no iNOS expression in healthy lungs.…”
Section: Resultsmentioning
confidence: 99%
“…Direct exposure of LPS to the lungs not only triggers pulmonary inflammation but also promotes oxidative stress significantly. [ 21 ] Thus, the LPS‐induced ALI model was also selected, which is considered to be the inflammatory disease with high expression of iNOS/ROS. [ 6b,22 ] As shown in Figure S31, Supporting Information, the quantitative detection results of iNOS and ROS content showed that, the content of iNOS in the injured lungs of ALI mice was 25.8 × 10 −6 m , and there was almost no iNOS expression in healthy lungs.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary delivery of nanomedicine is currently among the most propitious drug delivery alternatives to the lungs via inhalation. Drug bioavailability in the lungs might be improved compared to oral and parenteral routes, as the administration excludes gastrointestinal metabolism and first-pass effects in the liver [ 17 , 18 , 19 , 20 ]. This alternative approach also provides direct drug depositions on the desired site [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory diseases, asthma, chronic obstructive pulmonary disease (COPD) and lung cancer, as well as respiratory infectious diseases, pneumonia and tuberculosis (TB), have always been a serious issue to human’s society, not only threatening their lives but also negatively affecting their socioeconomic status (Parray et al 2021 ). In the group of viral pathogens, we see corona virus, adenovirus, respiratory syncytial virus, influenza virus, rhinovirus, and measles, which are responsible for viral pneumonia (He et al 2022 ). With the aim of treating either infectious respiratory diseases or systemic disorders, inhaled therapeutics reduce both applied dose and cost of therapy with benefiting patients to administer drugs individually or at a nursing home (Parray et al 2021 ).…”
Section: Local and Systemic Delivery Of Dried-powder Biopharmaceuticalsmentioning
confidence: 99%
“…Oligopeptides, cytokines, enzymes, vaccines, mAbs, genes and clotting factors are categorized as biopharmaceuticals (Osman et al 2018 ). Pulmonary delivery of biopharmaceutics could be promising for preparing higher bioavailability than other routes while delivering lower dose of therapeutics (He et al 2022 ). Local pulmonary system provides a rapid onset of action when it comes to low molecular weight drugs (Faghihi et al 2021 ).…”
Section: Local and Systemic Delivery Of Dried-powder Biopharmaceuticalsmentioning
confidence: 99%